The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/su11092513
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Integrated Sustainable Transportation Models for Electric Passenger Vehicle Diffusion

Abstract: Ensuring energy security, stopping climate change, and improving urban air quality are the three main challenges of this century that are being addressed by governments globally. The transportation sector contributes significantly to these issues. Sustainable transport involves the consideration of three dimensions—economic development, environmental preservation, and social development—and one of its aspects is the focus on the transition towards electric vehicles. The sustainable transportation is a complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…The difficulty of this approach, however, lies in the fact that the PTTMAM does not explicitly consider consumers' socio-economic characteristics and their heterogeneity across populations. This is also the case for three of the SD models reviewed by Lopez-Arboleda et al [21] (see their Table 4). Thus, there is an opportunity for further SD modelling work on detailed consumer characterization and disaggregation.…”
Section: Conclusion and Further Researchsupporting
confidence: 63%
See 1 more Smart Citation
“…The difficulty of this approach, however, lies in the fact that the PTTMAM does not explicitly consider consumers' socio-economic characteristics and their heterogeneity across populations. This is also the case for three of the SD models reviewed by Lopez-Arboleda et al [21] (see their Table 4). Thus, there is an opportunity for further SD modelling work on detailed consumer characterization and disaggregation.…”
Section: Conclusion and Further Researchsupporting
confidence: 63%
“…The use of disaggregate (multinomial (MNL) and nested MNL (NMNL)) models in EV market diffusion studies was identified by Gnann et al [20]. In their review of eleven models, Lopez-Arboleda et al [21] found that DCMs, especially MNL, were generally used to represent consumer purchases of electric passenger vehicles. According to these authors, Greene et al [22] and Kieckhäfer et al [23] applied NMNL.…”
Section: Literaturementioning
confidence: 99%
“…An interesting manuscript "The effect of perceived risk on the purchase intention of electric vehicles: an extension to the technology acceptance model" (Thilina, 2019) seeks to analyze significant market penetration for the sale of electric vehicles accompanied by the analysis (Mo, 2018) of life-cycle cost of ownership including congestion and environmental impacts (Tu, 2019), (Rajeev, et al, 2019), (Hao, 2017), (Philipsen, et al, 2019), (Lopez-Arboleda, et al, 2019), (Almeida, et al, 2019). Considerable emphasis have been placed on improvements in vehicle charging (Wolbertus, et al, 2019) amongst many other underlying technological areas seeking to improve the value proposition to potential buyers (Jager, et al, 2019), , , (Minnerup, et al, 2019), (Muller, 2019) and also make recommendations in both technology (Zha, et al, 2019), , (Zha, et al, 2019), , (Jiyan, et al, 2019), (Pier, et al, 2019), (Agaton, et al, 2019), , (Watanabe, et al, 2019), (Kusaka, et al, 2019), (Zhang, W., et al, 2019), , (Mayer, et al, 2019), (Ricciardi, et al, 2019), , (Yu, Z., et al, 2019), (Senda, et al, 2019), (Marquez-Fernandez, et al, 2019), (Wu, D., et al, 2019), (Wang, H., et al, 2019), (Obayashi, et al, 2019), (Gong, et al, 2019), (Vermeulen, et al, 2019), (Jia, J., et al, 2019), (Li, Q., et al, 2019) and policy incentives (Zhang, X., et al, 2019), (Ortar, et al, 2019), culminating in charging strategies to influence the obvious trade-off between gasoline prices and charging availability , (Wolbertus, et al, 2019),…”
Section: Materials (Literature Review)mentioning
confidence: 99%
“…This is especially necessary because Germans' travel behavior has become less sustainable during the coronavirus disease 2019 (COVID-19) pandemic: 20% of people indicate that they stopped using public transportation, and 17% plan to use a private car more frequently after the pandemic. The need for criteria and indicators to measure sustainability is evident through countless existing initiatives [18][19][20], such as the Transport and Environment Reporting Mechanism (TERM) [21] or the Global Reporting Initiative (GRI) [22].…”
Section: Introductionmentioning
confidence: 99%